Synergistic Effect of Terra Preta and Rice Straw Mulch on Growth and Yield of Hybrid Corn (Zea Mays L.) - Rikeu Relawati; Zakiyah Amini; Ananta Bayu Pratama (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Climate change challenges agriculture with altered rainfall and extreme temperatures. Terra preta and rice straw mulch can mitigate effects like drought and soil degradation. Terra preta, a carbon-rich black soil, improves soil structure, retains nutrients, and reduces atmospheric CO2. It can be made from organic waste. This study examines the impact of terra preta and rice straw mulch thickness on the growth and yield of hybrid maize cultivar Pertiwi 5. A factorial randomized block design (RBD) with two factors was applied: terra preta dose (0, 10, 15, and 20 tons/ha) and mulch thickness (0,3,6, and 9 cm). Data were analyzed using ANOVA for a linear model, with an F-test at a 5% significance level, followed by the Duncan Multiple Range Test (DMRT) for post hoc comparisons. Results showed the optimal treatment was 20 tons/ha of terra preta with 9 cm mulch, leading to a plant height of 181,544 cm, stem diameter of 36,4 mm, two cobs per plant, and the lowest dry weed weight of 26,33 g. The highest harvest index was with 15 tons/ha of terra preta and 9 cm mulch, at 77,87% and 77,77%. These findings suggest terra preta and rice straw mulch enhance maize growth and yield, providing a sustainable agriculture approach under climate change.